2010
DOI: 10.1590/s0102-311x2010001100019
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effect on nutrient intake in adults living in Southern Brazil

Abstract: The objective of this study was to investigate the effect of seasonality on nutrient intake in healthy adults from the southernmost metropolitan area of Brazil. The dietary intake (24-hour dietary recall on six different days) in a sample of 162 adults (114 women), aged 20 to 69, was obtained during the year 2007. The nutrient intake was averaged for each season and adjusted for energy intake using the residual method. The effect of season on energy, macro and micro-nutrient intake was investigated based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 30 publications
2
37
1
Order By: Relevance
“…Fat intake was lower in autumn but increased in spring. In contrast in a study conducted by Rassato et al in Brazil, the healthy adults consumed less fat in summer [7]. In shanghai women health study (SWHS) with 74,958 individuals, Fowke et al observed an increase in fat intake in winter [26].…”
Section: Discussionmentioning
confidence: 99%
“…Fat intake was lower in autumn but increased in spring. In contrast in a study conducted by Rassato et al in Brazil, the healthy adults consumed less fat in summer [7]. In shanghai women health study (SWHS) with 74,958 individuals, Fowke et al observed an increase in fat intake in winter [26].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the sources of variation in the FI of Brazilians studied are limited to methodological variations intrinsic to individuals. There were two studies 36,37 that showed results associating seasonality and FI in Brazil. In the first one, a variation was found in the eating behavior of workers with fixed shifts in the city of São Paulo between summer and winter by applying dietary recalls for three days.…”
Section: Tabela 3 -Médias De Ingestão (E Desvio-padrão -Dp) De Energimentioning
confidence: 99%
“…Rossato et al 37 analyzed the seasonal variation in FI of healthy adults living in the state of Rio Grande do Sul, Southern Brazil, Figure 1 -Percentage of adult men (a) and women (b) whose intakes, deattenuated by withinperson variation 17,18 , reached the recommendation for energy, macro and micronutrients intakes, in summer and winter, according to the Dietary Reference Intakes and the Brazilian Society of Cardiology [21][22][23][24][25][26][27] . Niterói, Rio de Janeiro, Brazil, 2007-8.…”
Section: Tabela 3 -Médias De Ingestão (E Desvio-padrão -Dp) De Energimentioning
confidence: 99%
“…However, results related to seasonal variations in dietary intake or availability as part of studies of modern diets have been inconsistent, with some finding evidence of seasonal variations [16,17] and some finding no seasonal variation [18,19]. With the development of modern agriculture, transportation, and food industries, the food supply is much more diverse than before and “off-season” food can be found on the table during most times of the year in developed cities like Shanghai.…”
Section: Introductionmentioning
confidence: 99%